Is YouTube a Reliable Resource for Osteoporosis Exercise Guidance? A Descriptive Cross-sectional Study - Serpil Çelik; Elif Tarihçi Çakmak (Türk Osteoporoz Dergisi, 2025)
Objective: The study aimed to evaluate the reliability, quality, and content analysis of English-language osteoporosis exercises videos on YouTube. Materials and Methods: On December 12, 2023, a search for “osteoporosis exercise” was conducted on YouTube. The 200 best-match English videos were included. The content, source, and characteristics were recorded. Reliability and quality were analyzed using the modified DISCERN (mDISCERN) score, Journal of the American Medical Association benchmark criteria, and global quality scale (GQS) score. Results: Of the 200 videos screened, 133 met the inclusion criteria. Of these, 8.2% (n=11) were presented by medical doctors, 51.8% (n=69) by physiotherapists or physical therapists, and 39.8% (n=53) by exercise specialists. GQS indicated that 15.0% (n=20) of the videos were high, 45.1% (n=60) medium, and 39.8% (n=53) poor quality. Videos featuring strengthening exercises and impact exercises had significantly higher GQS and mDISCERN scores compared to videos without these type of exercises. Conclusion: The majority of YouTube videos on “osteoporosis exercises” are of low quality and lack reliability. Medical doctors should prioritize sharing and demonstrating exercises to improve content quality and trustworthiness.